2021
DOI: 10.3389/fonc.2020.604657
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival in Nonsurgical Esophageal Cancer Patients Who Received Consolidation Chemotherapy Compared With Patients Who Received Concurrent Chemoradiotherapy Alone: A Systematic Review and Meta-Analysis

Abstract: BackgroundConcurrent chemoradiotherapy (CCRT) is the standard treatment for nonsurgical esophageal cancer (EC). However, esophageal cancer patients receiving CCRT alone are still unsatisfactory in terms of local control and overall survival (OS) benefit. Clinicians generally add consolidation chemotherapy (CCT) after CCRT. It remains controversial whether CCT following CCRT is beneficial for esophageal cancer. We, therefore, undertook a meta-analysis to assess the need for CCT in inoperable esophageal cancer.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…In our mind, our results were compatible with the results in the above-mentioned systematic review in that the point estimate of HR for OS was in favor of CCT [ 11 ]. In another systematic review published in 2021 (not limited to SqCC but consisted of mainly SqCC patients) [ 37 ], favorable OS (HR 0.72; 95% CI 0.59–0.86, P < 0.001) and response rate (OR 1.44; 95% CI 0.62–3.35, P = 0.393) were reported. Our results were relatively close to these results.…”
Section: Discussionmentioning
confidence: 99%
“…In our mind, our results were compatible with the results in the above-mentioned systematic review in that the point estimate of HR for OS was in favor of CCT [ 11 ]. In another systematic review published in 2021 (not limited to SqCC but consisted of mainly SqCC patients) [ 37 ], favorable OS (HR 0.72; 95% CI 0.59–0.86, P < 0.001) and response rate (OR 1.44; 95% CI 0.62–3.35, P = 0.393) were reported. Our results were relatively close to these results.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant chemotherapy is considered to eliminate circulating tumor cells in the blood to prevent distant metastasis of the tumor. 25 However, recurrence of esophageal cancer typically occur in situ, and chemotherapy therefore needs to reach the tumor tissue through blood circulation. As the esophageal blood supply after RT is reduced, the survival benefit is diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Although the RTOG 85-01 and PRODIGE-5 trials both took AC into account during their treatment design, the current guidelines do not recommend AC as a standard treatment [ 9 , 10 ]. The role of AC after CCRT has not been explored in randomized controlled clinical trials, and the retrospective studies have yielded mixed results [ 11 ]. Some researchers found that AC could not increase survival benefits, while others showed that AC could improve survival [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%